World development report 1991 : the challenge of development - The World Bank (Washington, D.C., 1991)
The book seeks to provide a comprehensive overview of the economic development agenda of the developing countries.
Includes bibliography pp.168-180
usc 01/09/2021
Loans
Keywords: Economic development; Nature and nurture; Adaptation (Biology); Economic history; Developing countries